Accelerated Stability Test of Snakehead Fish Extract (Channa striata) and Kelulut Honey (Heterotrigona itama) Ointment Combination with BHT as an Antioxidant - Mohamad Andrie; Wintari Taurina; Dyah Ayuningtias (Faculty of Pharmacy, Universitas Gadjah Mada, 2022)
The oil phase of adeps lanae was used as a basis in the ointment formulation with snakehead fish extract and kelulut honey, which influences wound healing. Adeps lanae has the potential to become rancid due to the high water content in it (25-30%). The use of oil-soluble antioxidants such as Butyl Hydroxy Toluene (BHT) can overcome the rancidity in oil. This study aimed to see how adding BHT as an antioxidant affects the ointment's stability. The ointment is prepared in three different BHT concentrations: F1 (0.0075%), F2 (0.05%), F3 (0.1%), and a control for comparison. Organoleptic tests, homogeneity, spreadability, adhesion, protection power, and acid number were used to evaluate the stability of the preparation over 28 days at 40 ± 2°C / RH 75 ± 5%. The data obtained were analyzed statistically using One Way ANOVA. The addition of BHT affected the preparation's spreadability, adhesion, and acid number but did not affect the organoleptic, homogeneity, or protective power. At F3, there is a significant difference in spreadability (5.57 ± 0.21 cm) and adhesion (89.00±2.00 seconds) based on statistical analysis. F3 is the best ointment based on the physical characteristics test results and the minimum increase in acid number (8.83 mg KOH/g).